Implementasi Sistem Informasi Bank Sampah Dengan Fitur Location Based Service Menggunakan Metode Waterfall - Putra Airudani; Murti Retnowo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A waste bank is a collection place for used goods to be processed and reused which has a system like banking in general but the transaction is used goods with a goods collector system providing prices according to the weight of used goods that have been predetermined, household needs everyday increase, namely the desire to buy new goods to meet these needs or also buy the same goods because of daily needs, With this new item also indirectly replaces the item that was once used. Therefore, an application is needed that can facilitate transactions between local residents and collectors from waste banks to transact directly and easily. The purpose of designing a waste bank application with the Location Based Service feature is to facilitate used goods transactions which are usually done manually and help overcome the management of used goods that are still ineffective until there is still a lot of waste wasted. The method used is the waterfall method which gradually starts from needs analysis, design, design to application experiments. The expected result of this research is that it can help people in the Nogotirto area become more enthusiastic about depositing their used goods so that it not only helps in reducing the disposal of inorganic waste or used goods that are thrown away in vain but can also help people earn money if they deposit used goods at the waste bank through this information system.